Eating Time as a Genetic Indicator of Methane Emissions and Feed Efficiency in Australian Maternal Composite Sheep - Sepulveda, Boris J.; Muir, Stephanie K.; Bolormaa, Sunduimijid; Knight, Matthew I.; Behrendt, Ralph; MacLeod, Iona M.; Pryce, Jennie E.; Daetwyler, Hans D. (Frontiers in Genetics, 2022)
Previous studies have reduced methane emissions (ME) and residual feed intake (RFI) with genomic selection in ruminants. The objective of this study was to evaluate feeding behaviour traits, such as the amount of time spent eating per day (eating time; ETD) and per visit (eating time per event; ETE) as genetic indicators for ME and RFI. Genotypes and phenotypes of 445 Australian Maternal Composite ewes at 3 different ages (post-weaning, hogget, and adult) were used to estimate the heritability of ME, RFI, feeding behaviour traits including ETD, ETE in addition to daily number of events (DNE), event feed intake (EFI; g/event) and eating rate (ER; g/min)) using univariate genomic best linear unbiased prediction models. Correlations between these traits and within each trait at different ages were estimated with multivariate models. The response to selection was evaluated for ME and RFI with direct selection models and indirect models with ETD and ETE as indicators traits, as these behaviour traits were the most promising indicator traits based on heritability and genetic correlations. Heritabilities were between 0.12 and 0.18 for methane emission traits and RFI, and between 0.34 and 0.46 for the eating behaviour traits. Selecting for a smaller ETD would reduce methane production per day, but it must be included in a selection index because it would slightly reduce body weight and growth. Selecting for more ETE would improve feed efficiency and produce more methane per day and per kg dry matter intake, but methane produced per kg of meat would not increase because more ETE is positively and strongly correlated with heavier animals. Selection for shorter ETD and longer ETE would select for less and larger meals, which could be of interest in production systems using supplements. Based on our results, ETD and ETE could be evaluated as indicator traits for ME and RFI under an index approach that allows to simultaneous selection for improvement in emissions, feed efficiency, and related traits. Selecting for eating time (ETD/ETE) could have a tremendous impact on the industry, as it may be easier and cheaper to obtain than feed intake and ME data.